LITERATURE REVIEW: KESADARAN DAN KESIAPAN DALAM MANAJEMEN BENCANA - Prasetyo, Wijar (JURNAL NERS LENTERA, 2019)
Introduction: Disaster events are unavoidable and have huge impact for victims so they need help from all parties concerned. Furthermore, system is needed to prepare for disasters through increased awareness and good preparation from related parties so disasters can be anticipated properly. The objective literature review is to review awareness and readiness in disaster management. Methods: Literature review is based on issues, methodology, equations and research. 5 studies used, 2 used qualitative studies, 1 used quantitative study and 2 used surveys and focus group discussions. The population is all parties related to disaster management and the sample is the community, nurses and the Health Department. Results: Based on 5 studies, it was found that disaster risk management in the community needed to increase awareness through education with traditional knowledge approaches and information dissemination, in order to the decision maker policy need clear system and structure including preparing health resources and in the hospital setting, it was necessary to inform management strategic plans disaster risk to nurses. Discussion: Awareness from the public, nurses or health workers and supported by a good Health Service disaster management system will create an area which is ready and responsive in dealing with existing disasters. Keywords: awareness, disaster risk management